PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA MATERI PERUBAHAN ENERGI KELAS IV SD NEGERI 76 PEKANBARU - Hasta Musawirna; Eka Murdani; Buyung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to: 1) Find out the influence of students' creative thinking abilities on flat building material on students after applying sticky board media to class IV students at SDN 01 Mandor; 2) Find out how much influence the sticky board media has on the material for flat shapes for class IV students at SDN 01 Mandor; 3) Knowing student responses to the application of flashcard media on creative thinking abilities in class IV students at SDN 01 Mandor. The type of research used is quantitative research. The population in this study were all fourth grade students at SDN 01 Mandor. Sampling in this study was carried out using saturated sampling, the sample consisted of 22 students consisting of class IV A SDN 01 Mandor. The data collection technique used in this research is a test technique in the form of learning outcomes in the cognitive domain and non-test in the form of a student response questionnaire.  This can be seen from the calculation of the effect size, namely 0.858 and the criteria are high because 0.858 is at ES > 0.8. 3) Positive student responses to the sticky board media in the creative thinking abilities of class IV students. This is shown from the calculations that the percentage of student responses of 63.59% is included in the high category.